2015
DOI: 10.1007/s00403-015-1612-9
|View full text |Cite
|
Sign up to set email alerts
|

Relation between sonic hedgehog pathway gene polymorphisms and basal cell carcinoma development in the Polish population

Abstract: In recent decades, increases have been observed in the incidence of nonmelanoma skin cancers, including basal cell carcinoma (BCC) and squamous cell carcinoma. BCC is the most common neoplasm in Caucasian populations. Sonic hedgehog (Shh) pathway impairment plays a key role in BCC pathogenesis, and there is evidence that Shh pathway genetic variations may predispose to BCC development. We genotyped 22 single-nucleotide polymorphisms (SNPs) in 4 Shh pathway genes: SHH, GLI, SMO, and PTCH. The study group consis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…Finally, the genotyping of the rs41313327 (C > T) demonstrated the prevalence of the homozygous genotype for the wild allele (C/C), following the frequencies reported in databases and even with previous investigations, in which patients with clinical conditions—other than cancer—had a similar frequency of the C allele to our studied groups, where the presence of the minor allele (T) was not detected either 46 . However, previous studies in BCC patients from the Polish population reported the frequencies of the C/C, C/T, and T/T genotypes with no differences between patients and controls 24 …”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Finally, the genotyping of the rs41313327 (C > T) demonstrated the prevalence of the homozygous genotype for the wild allele (C/C), following the frequencies reported in databases and even with previous investigations, in which patients with clinical conditions—other than cancer—had a similar frequency of the C allele to our studied groups, where the presence of the minor allele (T) was not detected either 46 . However, previous studies in BCC patients from the Polish population reported the frequencies of the C/C, C/T, and T/T genotypes with no differences between patients and controls 24 …”
Section: Discussionsupporting
confidence: 89%
“…46 However, previous studies in BCC patients from the Polish population reported the frequencies of the C/C, C/T, and T/T genotypes with no differences between patients and controls. 24 We also investigate a possible pathogenic effect in PROVEAN, SIFT, Polyphen, and FATHMM due to aminoacid change for exonic variants rs357564, rs2236405, and rs41313327 or splicing effect of intronic variant rs2297086 in regSNP-intron and Human Splicing Finder. [47][48][49][50][51][52] Although it was not conclusive, we could presume that the rs357564 may have a deleterious effect as we consider that the c-terminal domain is related to SMO protein retention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One previous analysis of patients with non-cancerous conditions in a Turkish population did not reveal the existence of the minor allele (T) [ 23 ]. In another previous report in a Polish population of patients with BCC, the C/C, C/T, and T/T genotypes were found, although without statistically significant differences between the patients and controls [ 60 ]. Similarly, the minor allele (A) of the rs2236405 variant has been documented with a low frequency, consistent with our results, in which the A allele was only identified in a few heterozygotes (T/A).…”
Section: Discussionmentioning
confidence: 98%
“…To date, several signaling pathways and molecules have been demonstrated to be involved in the tumorigenesis and progression of BCC at the molecular level, such as the hedgehog signaling pathway. 4 Genes included in this pathway, such as the hedgehog receptors patched (PTCH1) or smoothened (SMO), have been extensively studied. 5 , 6 Mutations in these genes may cause constitutive hedgehog pathway activation, which promote the development of BCC.…”
Section: Introductionmentioning
confidence: 99%